Age-related changes in relational encoding - Leow, Dayton Wei Yang (2013)
Reduced episodic encoding is a cognitive hallmark of an aging brain (Manentia et al., 2011). Episodic encoding involves a collaboration of both prefrontal cortex (PFC) and medial temporal lobe (MTL; Simons & Spiers, 2003). Converging evidence have shown the inferior frontal gyrus (IFG) to have increased co-activation with decreased activation in the MTL during episodic encoding in older adults. This may be consistent with posterior-to-anterior shift in aging (PASA) model (Davis et al., 2007) where older adults show increase in IFG (anterior of brain) activation to compensate for age-related reduction of activity in the hippocampus/parahippopampus (posterior of brain). Many studies have shown age-related changes in the functional activation of the MTL (including hippocampus /parahippocampus) and in frontal regions such as the IFG. Hence, it would be informative to evaluate the functional relationship of IFG and MTL if a PASA phenomenon is seen between the young and old adults. The present aging study utilized a functional MRI task sensitive to relational processing/encoding in young and old adults to evaluate age-related changes shown in functional neuroimaging. [1st Award]